Factors associated with acute stress reaction in pregnant with hyperemesis gravidarum hospitalized in the National Maternal Perinatal Institute, Lima, Peru (2021) - Silva-Dominguez, Daniel (2023)
Objective: To determine the factors associated with hyperemesis gravidarum and acute stress reaction in pregnant women with hyperemesis gravidarum hospitalized at the National Maternal Perinatal Institute during 2021. Materials and Methods: This research corresponds to an analytical, observational, case-control study, where the medical records of pregnant patients hospitalized for hyperemesis gravidarum attended by the psychology service who presented an acute stress reaction meeting the inclusion and exclusion criteria were collected. An analysis of frequencies and percentages of the different variables and a multivariate analysis were performed to find the significant factors (p<0.05) and the calculation of the Odds Ratio (OR) with a confidence level of 95%; this model was evaluated using multiple logistic regression. Results: A relationship was found between pregnancy planning (p<0.044, β=0.957 and OR=2.6047) and nausea rejection (p<0.028, β=1.774 and OR=5.893) in pregnant women with hyperemesis gravidarum. A direct relationship was found between the acute stress reaction in pregnant women with hyperemesis gravidarum, with respect to pregnancy loss (p<0.043, β=0.933 and OR=2.542) and hospitalization in the COVID-19 area (p<0.010, β=1.467 and OR=4.335); and inversely, regarding the acceptance of the pregnancy (p<0.014, β=-1.515 and OR=0.220). Conclusion: Two variables were found to be associated with the presence of hyperemesis gravidarum (pregnancy planning and the rejection of nausea). The acute stress reaction was related to two factors associated with the patients (gestational loss and pregnancy acceptance) and one associated with the pandemic (hospitalization in Covid-19 area) which explain 32% of the variance.